Determining the effect of oil after frying fish for the production of biofuels with a fractional composition of FAME - Wcisło, G.; Pracuch, B.; Tomyuk, V. (University of Engineering and Economics in Rzeszow, 2019)
The aim of the study was to determine the impact of the fish frying process on the distillation properties of FAME and its mixtures with diesel fuel. The fish was fried at 160 °C for 2 hours. Frying one serving lasted 6 minutes. The frying oil was a mixture of 50 % (v/v) rapeseed oil and 50 % (v/v) sunflower oil. The study showed that FAME biodiesel made from unused (pure) oil has similar distillation properties. The largest differences were observed for distillation temperatures of 85 % and 100 % and the final temperature of the distillation process. This may indicate a slightly lower purity of FAME produced from used cooking oil. In such a biofuel there may be more less volatile mono- and diglycerides or other chemicals that, e.g. after frying, remain in oil. It must be said, however, that they are not solid particles because they have been separated from the oil by filtration.
Keywords: Biodiesel; FAME – Fatty Acid Methyl Esters; diesel engine; fractional composition; temperature distillation